Monitoring PfMDR1 transport in Plasmodium falciparum - Reiling, Sarah J (Malar J, 2015)
BACKGROUND: The Plasmodium falciparum multidrug resistance 1 transporter, PfMDR1, contains five amino acid polymorphisms that are suggested to be involved in altered drug transport from the parasite’s cytosol into the digestive vacuole (DV). Transport of a substrate into another intracellular compartment influences drug availability at its site of action, therefore making the parasite more susceptible or resistant to a drug. Fluo-4 is a known fluorescent substrate that can be used as a molecular tool to investigate transport dynamics of PfMDR1 in many parasite strains. METHODS: Six P. falciparum strains with varying PfMDR1 mutations were loaded with Fluo-4 AM. Accumulation of the fluorophore in the DV was measured using confocal microscopy. The role of a key amino acid mutation was verified using selected parasite clones with point mutations at PfMDR1 amino acid position 1042. Equal expression of PfMDR1 was confirmed by Western blot. RESULTS: Fluo-4 was transported by PfMDR1 into the DV of most drug-sensitive and -resistant parasites. Asparagine at PfMDR1 amino acid position 1042 was crucial for Fluo-4 transport, while the N1042D substitution abolished Fluo-4 transport. Competition studies of Fluo-4 with chloroquine, quinine and mefloquine were performed on parasites harbouring asparagine at position 1042. A distinct Fluo-4 transport inhibition pattern for each tested anti-malarial drug was observed in parasite strains of different genetic background. CONCLUSION: This study demonstrates that Fluo-4 can be used to investigate PfMDR1 transport dynamics in both drug-sensitive and -resistant parasites. Furthermore, direct evidence of altered Fluo-4 transport in PfMDR1 is linked to a single amino acid mutation in the substrate binding pocket. This system offers a great tool to investigate the role of substrate transport by PfMDR1 and the mutations necessary to support transport, which would lead to new insights for the development of novel anti-malarial drugs. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12936-015-0791-3) contains supplementary material, which is available to authorized users.